ACADEMIC ETHICS OF STUDENT COMMUNICATION WITH LECTURERS IN SOCIAL MEDIA - Ramadan Lubis; Aulia Khairani Harahab; Ayu Saniah Sihotang (Sufiya Journal of Islamic Studies, 2023)
Communication is the process of sending and receiving messages between two ormore people. In the millennial era, now communication tools are increasingly sophisticated,but are considered as one of the triggers for problems related to ethics in communication.This study aims to describe the ethics of communicating with lecturers, recognizing varioustypes of social media, and knowing how to communicate properly and correctly withlecturers. This paper uses qualitative research methods with the type of library research, inwhich the data is generated from books, scientific journals, mass media and the internet aswell as other relevant references. The results of the study show that there are ways or rulesthat regulate a person's communication in order to achieve effective communication, and thestandards for writing messages sent by students to lecturers should pay attention to the timeof delivery, message format, and language